The effectiveness of rehabilitation of female prisoners in Zimbabwe: the case of Chikurubi Female Prison - Magadzire, Mitchelle T. (Midlands State University, 2019)
The purpose of this research was to examine the effectiveness of rehabilitation of female prisoner in Zimbabwe in case of Chikurubi Female Prison.in particular this include the rehabilitation mechanisms which were introduced at Chikurubi with the purpose of reforming inmates and to prepare them for the reintegration process. The rehabilitation mechanisms include vocational training which involves programmes such as hairdressing, cosmetology, chicken rearing, tailoring, secretariat, knitting and cooking and hospitality also psychosocial rehabilitation which include counselling services, recreational activities which involves dramas, different sports and traditional dance, spiritual activities which involves bible study, choral singing and spiritual counselling and education activities which involves the provision of education from primary to tertiary level . Particular attention was given to examine the plight of female prisoners in Zimbabwe and this involves stigmatization, victimization lack of access to medical facilities, lack of pre natal and post natal care for pregnant mothers and nursing mothers and also the successes and challenges of the rehabilitation mechanisms. Only a sample of 50 women which involved the inmates, ex inmates and rehabilitation officers were selected as respondents. Semi-structured questionnaires and interviews were used to collect the information from the selected respondents. The results were based on the information captured in the questionnaires and qualitative face to face interactions. The research acknowledged that rehabilitation mechanisms have managed to be good and helpful to the inmates, also there are helpful in preparing inmates for pre-release and the equip inmates with new skills to search for employment. This alluded that some of the respondents were a living testimony of this process. However they were enormous challenges which is hindering the effectiveness of rehabilitation of female prisoners and this include presidential pardon, lack of resources, county’s economic hardships , lack of a robust monitoring and evaluation of the rehabilitation mechanisms and lack of a budget allocation for the implementation of the rehabilitation programmes just to mention but a few.